Home, Beyond a Place of Living A study of Indian Partition 1947 in Indian Cinema - Rochak Saxena (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2022)
Indian cinema has been talking about serious issues since its inception, whether it is pragmatic issues like poverty and family relations, or sensitive ones like communal fracas or partition of the nation in 1947 after its independence from a prolonged British rule. The representation of the event, and how filmmakers tackle the responsibility of portraying such delicate subjects. While 1947 rang in with joy of freedom after staying under British rule for over 250 years, tragedy struck in the form of partition, giving birth toIndia and Pakistan. Freedom came with a price; communal riots occurred, and millions of people lost their lives from the newly created sides during the exodus. This resulted from people of both sides of the border wanting to call a piece of land their home. To be able to identify with a place as home caused a deadly revolt, more to do with the religious identity, for it forced some to leave the home (place) they inhabited for years. Also, it involved forced migration of about 12 million people who moved across the border to their newly identified homes in India and Pakistan (Roy, A.G., & Bhatia, N., 2008). Using the qualitative approach for the study with content analysis using coding technique, the researcher employs the elements of Realist Film Theory, Apparatus Film Theory, Marxist Film Theory, and Cognitive Film Theory to study and analyze the select Indian films between 1970 and 2020. Mehta, R. B., & Mookerjea-Leonard, D. (2014) say that although Indian cinema began witnessing the representation of partition by late 1940s, it is only recently in the last few decades that film scholars have begun to analyze the films, made in larger numbers in contemporary period. The researcher not only studies how the films have represented the partition but also the effect on societies and families as a result of losing the old and eventually making a new home. The movies covering the spectrum of the portrayal of an eventbelong to two different paths of Indian Cinema, the first being Mainstream (Commercial) cinema and the second one Parallel cinema movement of India. The films selected are Garm Hava (1973), Tamas (1988), Tahader Katha (1992), Train to Pakistan (1998), Shaheed-e-Mohabbat Boota Singh (1999), Gadar: Ek Prem Katha (2001), Pinjar (2003), Bhaag Milkha Bhaag (2013), Toba Tek Singh (2017), and Manto (2018), adhering to the notion of home. The study directs to indicate that the imagery is linked with either the realistic or fabricated approach of the issue and is eventually made to elicit a particular emotion in the audiences. The definitive idea of home is explored not only as a place for living, but also working on a mental level as a concept of memory for the characters of the film.